Producción de Piaractus brachypomus “paco” y Cucumis sativus “pepino” en sistema acuapónico - Rodriguez Torres, Rafael (2023)
The objective of this study was to evaluate the production of paco, Piaractus brachypomus and Cucumis sativus cucumber in an aquaponic system, which consisted of a hydroponic element and an aquaculture element. The fish were conditioned in 1m3 wooden troughs and the plants in 0.24m3 culture beds. The completely random design was used, with the treatments (T1=30 fish/m3; T2=40 fish/m3) and 4 repetitions, with 8 experimental units. At the end of the trial, it was observed that the fish from the T1 treatment reached greater growth in length (14.5 cm) and weight (56.1 g). Statistically significant differences (p0.05), while those of the water reached permissible ranges for the studied species.